Information and communication technologies in the work of the Eurasian transport corridors (case of the EAEU countries) - Z. A. Dadabaeva; E. A. Savicheva (Проблемы постсоветского пространства, 2023)
Digitalization of the economy is proclaimed as a main target by  all countries of the Eurasian Economic Union. The official authorities are doing a lot  but  despite the efforts being made, the goals  have not been fully achieved. It is especially sensitive for traffic flows, which in modern geopolitical realities acquire a special role in the world trade operations. The EAEU countries started transition to modern technologies long before the events in 2022. The main aim was not only to create conditions for economic growth (reducing the terms of passenger and freight transportation, simplifying transit through the EAEU, reducing financial costs, creating a barrier-free trading environment), but also increasing the attractiveness of the economic union for other states.Currently, digitalization processes have an impact on integration processes, determining the future of export-import operations. Building effective and technological supply chains increases the transport transit potential of the EAEU and its neighboring states, creates conditions for the implementation of large projects to modernize the transport infrastructure. The analysis of the state and role of information and communication technologies in the movement of goods inside and outside the EAEU, along existing and new logistics corridors, undertaken in the article, showed that the countries of the Union continue to create favorable conditions for business, gradually erasing the borders between states at the digital level, reducing the existing restrictions.